PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT DENGAN MENGGUNAKAN MEDIA PUZZLE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DI KELAS IV SDN KALIRUNGKUT IV/580 SURABAYA - Wahyuni, Dita Eka; Warsono, Warsono; Subroto, Waspodo Tjipto (Universitas Negeri Surabaya, 2020)
ABSTRACTThe purpose of this reasearch is to describe the increase of students activity and studying achievement in applying the Teams Games Tournament learning model by using puzzle on Subthee the beauty of cultural diversity of my country in the fourth grade of SDN Kalirungkut IV/580 Surabaya. This research is a class action research (PTK). This research is conductedin three cycles in which each cycles needs four steps or phases, they are planning, implementation, observation and reflection. The data collection is obtained through observation and test. The subjects of this research are 26 fourth grade students of SDN Kalirungkut IV/580 Surabaya which consist of 16 male students and 10 female students. The result shows that the application of the cooperative type Teams Games Tournament learning model by using puzzle game can increase the students activity and studying achievement. It can be seen from the result of the research which shows the students activity enchancement from cycle I clasically teached 56% and include the category of enought mastery. In cycle II the students activity reached 70% and also include the category enough mastery. In cycle III it reached 82% and include the category of good mastery. The mastery percentage of the students studying achievement in cycle I clasically reached 46% (12 students). While in cycle II, it increased up to 77% (19 students) and more increased up to 85% (22 student) in cycle III which shows activity enchancement from cycle I until cycle IIIKeyword : Teams Games Tournament learning model ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan peningkatan aktivitas dan hasil belajar siswa dalam penerapan model pembelajaran teams games tournament menggunakan media puzzle pada subtema indahnya keragaman budaya negeriku di kelas IV SDN Kalirungkut IV/580 Surabaya. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK).Penelitian dilaksanakan dalam tiga siklus di mana masing-masing siklus dilalui dengan empat tahapan, yaitu (1) perencanaan; (2) pelaksanaan; (3) observasi; (4) refleksi.Pengumpulan data diperoleh melalui observasi dan tes.Subjek penelitian ini adalah siswa kelas IV SDN Kalirungkut IV/580 dengan jumlah 26 siswa yang terdiri atas 16 siswa laki-laki dan 10 siswa perempuan. Hasil penelitian menunjukan bahwa penerapan model pembelajaran kooperatif tipe Teams Games Tournament (TGT) dengan media permainan puzzle dapat meningkatkan aktivitas dan hasil belajar siswa. Hal ini terbukti dengan hasil penelitian menunjukkan terjadi peningkatan aktivitas siswa dari siklus I secara klasikal mencapai 56% masuk kategori ketuntasan cukup.Siklus II aktivitas siswa mencapai 70%masuk kategori ketuntasan cukup.Pada siklus III mencapai 82% atau kategori ketuntasan baik.Persentase ketuntasan hasil belajar siswa secara klasikal siklus I mencapai 46% atau 12 siswa yang tuntas. Sedangakan pada siklus II mengalami peningkatan menjadi 77% atau 19 siswa tuntas dan meningkat lagi menjadi 85% atau 22 siswa pada siklus III.Kata Kunci: Model Kooperatif Teams Games Turnement.